Atomistic investigation of the impact of stress during solid phase epitaxial regrowth. Issue 1 (9th December 2013) - Sklenard, Benoit; Barbe, Jean‐Charles; Batude, Perrine; Rivallin, Pierrette; Tavernier, Clement; Cristoloveanu, Sorin; Martin‐Bragado, Ignacio; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract An atomistic model to account for the impact of stress during solid phase epitaxial regrowth (SPER) is proposed. This model is based on the lattice kinetic Monte Carlo method. It has been compared with experimental data of regrowth velocity as a function of hydrostatic and non‐hydrostatic stresses. In particular, it permits to provide a physical explanation of the observations upon in‐plane uniaxial stress based on the assumption that {100} events occur through a dual‐timescale atomistic mechanism. Our model also catches the fact that compressive normal uniaxial stress and hydrostatic pressure result in an enhancement of the regrowth velocity with a similar activation volume. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)